2019
DOI: 10.1007/978-3-030-25540-4_25
|View full text |Cite
|
Sign up to set email alerts
|

VerifAI: A Toolkit for the Formal Design and Analysis of Artificial Intelligence-Based Systems

Abstract: We present VERIFAI, a software toolkit for the formal design and analysis of systems that include artificial intelligence (AI) and machine learning (ML) components. VERIFAI particularly seeks to address challenges with applying formal methods to perception and ML components, including those based on neural networks, and to model and analyze system behavior in the presence of environment uncertainty. We describe the initial version of VERIFAI which centers on simulation guided by formal models and specification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
127
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 21 publications
(40 reference statements)
1
127
0
Order By: Relevance
“…7. The results confirmed the importance of model and color (compare (2) to (7)), as well as angle (compare (5) to (6)), but also suggested that being close to the camera could be the relevant aspect of the car's local position. We confirmed this with a final round of scenarios (compare (5) and (8)), which also showed that the effect of car model is small among scenes where the car is close to the camera (compare (4) and (9)).…”
Section: Training On Rare Eventssupporting
confidence: 75%
See 3 more Smart Citations
“…7. The results confirmed the importance of model and color (compare (2) to (7)), as well as angle (compare (5) to (6)), but also suggested that being close to the camera could be the relevant aspect of the car's local position. We confirmed this with a final round of scenarios (compare (5) and (8)), which also showed that the effect of car model is small among scenes where the car is close to the camera (compare (4) and (9)).…”
Section: Training On Rare Eventssupporting
confidence: 75%
“…In future work we plan to conduct experiments applying Scenic to a variety of additional domains, applications, and simulators. For example, we have integrated Scenic as the environment modeling language for VerifAI, a tool for the design and analysis of AI-based systems [7], and used it to generate seed inputs for temporal-logic falsification of an automated collision-avoidance system. We have also interfaced Scenic to the X-Plane flight simulator [36] in order to test ML-based aircraft navigation systems, and to the CARLA driving simulator [6] for scenarios requiring more control than GTAV provides.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While formal verification is desirable, in practice, it can be difficult due to high system complexity, unavailability of source code, and limited capacity of existing verification tools. In addition, many systems have started incorporating machine learning components, which remain challenging to test or verify [13], [21].…”
Section: Introductionmentioning
confidence: 99%